Asphalt concrete and preparation method thereof
By adding specific fibers and materials to asphalt concrete, the bonding strength between fibers and asphalt is improved, the problem of insufficient mechanical properties of existing asphalt concrete is solved, and significant performance improvement is achieved.
Patent Information
- Application Number
- CN202410533801.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-04-30
AI Technical Summary
The existing asphalt concrete still has shortcomings in its mechanical properties and cannot meet the needs of the development of the times.
By adding basalt fibers, hollow alumina-zirconia fibers, fly ash, iron tailings powder and silane coupling agents to the asphalt concrete, the dispersion and bonding strength of the fibers in the asphalt are improved and the mechanical properties of the concrete are enhanced.
It significantly improves the compressive strength, flexural strength and other mechanical properties of asphalt concrete, making it have excellent application prospects.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of concrete, and more specifically, relates to an asphalt concrete and a preparation method thereof. Background Art
[0002] Asphalt concrete is a multiphase composite material formed by mixing asphalt, aggregates and fillers in a certain proportion. Asphalt concrete has good ductility and can better adapt to deformation caused by geological activities and building settlement. Its excellent anti-seepage performance makes it widely used in anti-seepage projects of water conservancy and hydropower projects.
[0003] With the development of asphalt concrete, the requirements for its performance are getting higher and higher. With the development of fiber materials, the performance of asphalt concrete has been improved after adding fiber. Fiber can significantly improve the crack resistance, impact resistance and toughness of concrete, which greatly improves the disaster prevention, mitigation and post-disaster repair capabilities of buildings and structures.
[0004] CN117902858A discloses a foamed lightweight concrete and its preparation method and foundation structure, the foamed lightweight concrete includes the following components by weight: 150-200 parts of cement; 100-250 parts of fly ash; 30-55 parts of silica ash; 10-25 parts of organic silicon resin; 2-5 parts of mixed fiber; 2.5-4 parts of foaming agent; 240-320 parts of water; wherein the mixed fiber includes at least two of modified basalt fiber, polypropylene fiber, alkali-resistant glass fiber, polyvinyl alcohol fiber, and regenerated bamboo fiber. The lightweight concrete is light in weight, uniform and stable in texture, good in compression and flexural properties, high in composite strength and good in durability; it is suitable for unstable foundations such as slopes and terraces, can reduce deadweight, has high structural strength, and can well ensure the safety and stability of the foundation.
[0005] CN117902874A discloses a fast-hardening high-strength steel fiber reinforced concrete and a preparation method thereof. A fast-hardening high-strength steel fiber reinforced concrete, the preparation raw materials include, by weight: 450-530 parts of sulphoaluminate cement, 150-180 parts of Portland cement, 134-198 parts of gypsum, 400-1025 parts of quartz sand, 200-650 parts of bauxite, 187-240 parts of silica fume, 20-67 parts of heavy calcium powder, 134-217 parts of steel fiber, 23-67 parts of water reducer, 204-331 parts of water; the above scheme reduces the risk of concrete cracking, improves the strength of concrete, and reduces the amount of cement used, thereby reducing the production cost of concrete through the synergistic effect of sulphoaluminate cement, Portland cement, gypsum, quartz sand, bauxite, silica fume, heavy calcium powder, steel fiber, water reducer and water.
[0006] CN116606555A discloses a high elastic modified asphalt, asphalt concrete and a preparation method thereof. The high elastic modified asphalt comprises the following raw materials in parts by weight: 70 to 80 parts of base asphalt, 10 to 16 parts of asphalt plasticizer, 10 to 14 parts of high elastic modifier, and 10 to 20 parts of stabilizer, wherein the stabilizer comprises anti-ultraviolet modified fiber, alkaline binding carrier and accelerator, and the weight ratio of the anti-ultraviolet modified fiber, alkaline binding carrier and accelerator is 1:6 to 15:3. The high elastic modified asphalt of the present application can be used for bridge deck paving in high-altitude mountainous areas, and has the advantage of reducing the adverse effects of ultraviolet radiation on the strength of high elastic modified asphalt concrete.
[0007] CN117886568A discloses a high temperature resistant concrete and a preparation method thereof, comprising the following components by weight: 300-1400 parts of cement, 150-250 parts of magnesium slag, 30-60 parts of forsterite whiskers, 700-1000 parts of wollastonite, 100-200 parts of mineral admixtures, 350-600 parts of sand, 60-100 parts of wollastonite fibers, 80-150 parts of steel fibers, 150-180 parts of water and 10-18 parts of water reducing agent. The concrete in the prior art has poor high temperature resistance, and fire causes concrete cracking and serious structural damage.
[0008] The comprehensive performance of concrete can be improved by adding fiber materials to concrete, but there are still deficiencies in improving the mechanical properties and it cannot meet the needs of the development of the times. Summary of the invention
[0009] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art and provide an asphalt concrete and a preparation method thereof. In parts by weight, it includes the following components: 15-25 parts of asphalt; 10-20 parts of basalt fiber; 4-8 parts of hollow alumina-zirconia fiber; 20-30 parts of fly ash; 30-40 parts of iron tailings powder; 25-29 parts of water; 6-10 parts of silane coupling agent. By adding a silane coupling agent, the dispersion of the fiber in the asphalt can be improved, and the bonding strength between the fiber and the asphalt can be improved, thereby affecting the improvement of the mechanical properties of the asphalt concrete; by adding fiber materials, it has the effects of bridging and reinforcement, grid constraint and cross-section enhancement, so that the various properties of the asphalt concrete are improved. That is, the concrete prepared by the present invention has excellent application prospects.
[0010] The purpose of the present invention is to provide an asphalt concrete.
[0011] Another object of the present invention is to provide a method for preparing asphalt concrete.
[0012] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0013] An asphalt concrete, comprising the following components in parts by weight:
[0014] Asphalt 15-25 parts;
[0015] Basalt fiber 10-20 parts;
[0016] 4 to 8 parts of hollow alumina-zirconia fibers;
[0017] 20-30 parts of fly ash;
[0018] 30-40 parts of iron ore tailings powder;
[0019] 25-29 parts water;
[0020] Silane coupling agent 6-10 parts.
[0021] Preferably, the basalt fiber has a length of 5 to 7 mm and a diameter of 6 to 8 μm.
[0022] Preferably, the particle size of the fly ash is 0.1-0.5 mm.
[0023] Preferably, the particle size of the iron tailings powder is 2 to 4 mm; and the silane coupling agent is at least one of A-1120 and KH-792.
[0024] In the present invention, a preferred technical solution is that the method for preparing the hollow alumina-zirconia fiber comprises the following steps:
[0025] Zirconium n-butoxide, aluminum acetate and polyvinyl pyrrolidone are ultrasonically dispersed in DMF and electrospun. Cobalt oxide / zirconium oxide hollow fibers are obtained after pre-oxidation and heating and calcination in a muffle furnace.
[0026] Preferably, the mass ratio of the zirconium n-butoxide, aluminum acetate and polyvinyl pyrrolidone is 1:0.2-0.4:1-1.6; the ratio of the zirconium n-butoxide to DMF is 1 g:8-16 mL.
[0027] Preferably, the voltage of the electrospinning is 12-14 kV, and the distance between the syringe needle and the receiving plate is 24-28 cm.
[0028] Preferably, the pre-oxidation temperature is 140-180° C., and the pre-oxidation time is 3-7 hours.
[0029] Preferably, the calcination temperature is 400-600°C and the reaction time is 3-7h.
[0030] A method for preparing asphalt concrete based on the above-mentioned method comprises the following steps:
[0031] (1) Basalt fiber, hollow alumina-zirconia fiber, fly ash, iron tailings powder, silane coupling agent and water are mixed, heated to 60-80° C. and stirred for 1-2 hours; then asphalt is added, and the temperature is subsequently raised to 140-170° C. and stirred for 2-4 hours to obtain asphalt concrete.
[0032] The present invention has the following beneficial effects:
[0033] The present invention can improve the dispersibility of fiber in asphalt by adding silane coupling agent, improve the bonding strength between fiber and asphalt, and thus affect the improvement of mechanical properties of asphalt concrete; by adding fiber materials, especially by compounding basalt fiber and hollow alumina-zirconia fiber, it has more excellent bridging and reinforcement, grid constraint and cross-section enhancement effects, so that various properties of asphalt concrete are significantly improved. That is, the concrete prepared by the present invention has excellent application prospects. DETAILED DESCRIPTION
[0034] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0035] Among them, the asphalt is No. 90 (A) grade road petroleum asphalt;
[0036] Iron tailings powder: The chemical components of iron tailings powder are SiO2, Al2O3, Fe2O3, MgO, CaO, SO3, Na2O and K2O, and the percentage of each of the above chemical components in the total amount of iron tailings powder is 61.86%, 14.47%, 6.92%, 10.29%, 3.15%, 1.41%, 1.32% and 0.58%, respectively.
[0037] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0038] Example 1
[0039] An asphalt concrete, comprising the following components in parts by weight:
[0040] Asphalt 20 parts;
[0041] 15 parts of basalt fiber; the length of basalt fiber is 6 mm; the diameter is 7 μm;
[0042] 6 parts of hollow alumina-zirconia fibers;
[0043] 25 parts of fly ash; the particle size of the fly ash is 0.3 mm;
[0044] 35 parts of iron tailings powder; the particle size of the iron tailings powder is 3 mm;
[0045] 27 parts water;
[0046] 8 parts of silane coupling agent; the silane coupling agent is A-1120;
[0047] The method for preparing hollow alumina-zirconia fibers comprises the following steps:
[0048] 10 g of zirconium n-butoxide, 3 g of aluminum acetate and 14 g of polyvinyl pyrrolidone were ultrasonically dispersed in 120 mL of DMF for electrospinning. The electrospinning voltage was 13 kV and the distance between the syringe needle and the receiving plate was 26 cm. Under air atmosphere, hollow alumina-zirconia fibers were obtained after pre-oxidation at 160°C for 5 h and calcination at 500°C in a muffle furnace for 5 h.
[0049] A method for preparing asphalt concrete comprises the following steps:
[0050] (1) Basalt fiber, hollow alumina-zirconia fiber, fly ash, iron tailings powder, silane coupling agent and water were mixed, heated to 70° C. and stirred for 1.5 h; then asphalt was added, and the temperature was subsequently raised to 155° C. and stirred for 3 h to obtain asphalt concrete.
[0051] Example 2
[0052] An asphalt concrete, comprising the following components in parts by weight:
[0053] Asphalt 25 parts;
[0054] 10 parts of basalt fiber; the length of basalt fiber is 7 mm; the diameter is 8 μm;
[0055] 8 parts of hollow alumina-zirconia fibers;
[0056] 20 parts of fly ash; the particle size of the fly ash is 0.1 mm;
[0057] 40 parts of iron tailings powder; the particle size of the iron tailings powder is 4 mm;
[0058] 29 parts water;
[0059] 6 parts of silane coupling agent; the silane coupling agent is KH-792;
[0060] The preparation method and conditions of the hollow alumina-zirconia fibers are the same as those in Example 1.
[0061] A method for preparing asphalt concrete comprises the following steps:
[0062] (1) Basalt fiber, hollow alumina-zirconia fiber, fly ash, iron tailings powder, silane coupling agent and water were mixed, heated to 80° C. and stirred for 1 h; then asphalt was added, and the temperature was subsequently raised to 170° C. and stirred for 2 h to obtain asphalt concrete.
[0063] Example 3
[0064] An asphalt concrete, comprising the following components in parts by weight:
[0065] Asphalt 15 parts;
[0066] 20 parts of basalt fiber; the length of basalt fiber is 5 mm; the diameter is 6 μm;
[0067] 4 parts of hollow alumina-zirconia fiber;
[0068] 30 parts of fly ash; the particle size of the fly ash is 0.5 mm;
[0069] 30 parts of iron tailings powder; the particle size of the iron tailings powder is 2 mm;
[0070] 25 parts water;
[0071] 10 parts of silane coupling agent; the silane coupling agent is KH-792;
[0072] The preparation method and conditions of hollow alumina-zirconia fibers are the same as those in Example 1.
[0073] A method for preparing asphalt concrete comprises the following steps:
[0074] (1) Basalt fiber, hollow alumina-zirconia fiber, fly ash, iron tailings powder, silane coupling agent and water were mixed, heated to 60° C. and stirred for 2 h; then asphalt was added, and the temperature was subsequently raised to 140° C. and stirred for 4 h to obtain asphalt concrete.
[0075] Example 4
[0076] On the basis of Example 1, the weight proportion of the silane coupling agent remains unchanged, except that the silane coupling agent is A-1120 and KH-792; the mass ratio of A-1120 to KH-792 is 3:1. Other processes and conditions remain the same as in Example 1.
[0077] Comparative Example 1
[0078] Comparative Example 1 is substantially the same as Example 1, except that an equal amount of hollow zirconia fibers is used to replace hollow alumina-zirconia fibers. The method for preparing the hollow zirconia fibers comprises the following steps:
[0079] 13 g of zirconium n-butoxide and 14 g of polyvinyl pyrrolidone were ultrasonically dispersed in 120 mL of DMF for electrospinning. The voltage of the electrospinning was 13 kV, and the distance between the syringe needle and the receiving plate was 26 cm. After pre-oxidation at 160° C. for 5 h and calcination at 500° C. for 5 h in a muffle furnace, hollow fibers were obtained.
[0080] Comparative Example 2
[0081] Comparative Example 2 is substantially the same as Example 1, except that basalt fiber is used to replace basalt fiber and hollow alumina-zirconia fiber, wherein the weight portion of basalt fiber is 15 parts.
[0082] Comparative Example 3
[0083] Comparative Example 3 is substantially the same as Example 1, except that basalt fiber is used to replace basalt fiber and fly ash, wherein the weight proportion of basalt fiber is 40 parts.
[0084] Comparative Example 4
[0085] Comparative Example 4 is substantially the same as Example 1, except that fly ash is used to replace fly ash and iron tailings powder, wherein the weight proportion of fly ash is 60 parts.
[0086] Comparative Example 5
[0087] Comparative Example 5 is substantially the same as Example 1, except that the pre-oxidation and calcination processes are performed under a nitrogen atmosphere.
[0088] The asphalt concrete prepared in Examples 1 to 3 and Comparative Examples 1 to 5 was subjected to relevant mechanical property tests according to GB / T50784-2013 standard. The specific test results are shown in Table 1:
[0089] Table 1
[0090] Compressive strength(MPa) Flexural strength(MPa) Example 1 95.4 81.9 Example 2 93.8 80.9 Example 3 94.3 81.1 Example 4 98.9 88.2 Comparative Example 1 91.4 77.8 Comparative Example 2 86.7 73.2 Comparative Example 3 87.9 74.6 Comparative Example 4 89.2 75.4 Comparative Example 5 92.4 79.8
[0091] It can be seen from Table 1 that the asphalt concrete prepared by the present invention has a maximum compressive strength of 98.9 MPa and a maximum flexural strength of 88.2 MPa. Moreover, by comparing the examples with the comparative examples, it can be seen that the components of the present application have a synergistic effect, and it also proves that the asphalt concrete prepared by the present invention has excellent mechanical properties.
[0092] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An asphalt concrete, characterized in that: By weight, it includes the following components: Asphalt 15-25 parts; Basalt fiber 10-20 parts; 4 to 8 parts of hollow alumina-zirconia fibers; 20-30 parts of fly ash; 30-40 parts of iron ore tailings powder; 25-29 parts water; Silane coupling agent 6-10 parts; The preparation method of the hollow alumina-zirconia fiber comprises the following steps: The method comprises the following steps: ultrasonically dispersing zirconium n-butoxide, aluminum acetate and polyvinyl pyrrolidone in DMF, performing electrostatic spinning, and obtaining cobalt tetroxide / zirconium oxide hollow fibers after pre-oxidation and heating and calcining in a muffle furnace; wherein the mass ratio of zirconium n-butoxide, aluminum acetate and polyvinyl pyrrolidone is 1:0.2-0.4:1-1.6; The silane coupling agents are A-1120 and KH-792; the mass ratio of A-1120 to KH-792 is 3:
1.
2. The asphalt concrete according to claim 1, characterized in that: The length of the basalt fiber is 5-7 mm, and the diameter is 6-8 μm.
3. The asphalt concrete according to claim 1, characterized in that: The particle size of the fly ash is 0.1-0.5 mm.
4. The asphalt concrete according to claim 1, characterized in that: The particle size of the iron tailings powder is 2 to 4 mm.
5. The asphalt concrete according to claim 1, characterized in that: The ratio of zirconium n-butoxide to DMF is 1 g:8-16 mL.
6. The asphalt concrete according to claim 1, characterized in that: The voltage of the electrostatic spinning is 12-14 kV, and the distance between the syringe needle and the receiving plate is 24-28 cm.
7. The asphalt concrete according to claim 1, characterized in that: The pre-oxidation temperature is 140-180° C., and the pre-oxidation time is 3-7 hours.
8. The asphalt concrete according to claim 1, characterized in that: The calcination temperature is 400-600° C., and the reaction time is 3-7 hours.
9. A method for preparing asphalt concrete according to any one of claims 1 to 8, characterized in that: The steps include: (1) Basalt fiber, hollow alumina-zirconia fiber, fly ash, iron tailings powder, silane coupling agent and water are mixed, heated to 60-80° C. and stirred for 1-2 hours; then asphalt is added, and then the temperature is raised to 140-170° C. and stirred for 2-4 hours to obtain asphalt concrete.
Citation Information
Patent Citations
High-temperature-resistant concrete and preparation method thereof
CN117886568A
Foam lightweight concrete, preparation method thereof and foundation structure
CN117902858A
Quick-hardening high-strength steel fiber reinforced concrete and preparation method thereof
CN117902874A
Asphalt concrete pavement construction method
CN112012068A